The Significance of Changes of Source Areas During Carboniferous Turbiditic Deposition (Southwestern Iberia) - Pereira, Manuel Francisco (2015)
U–Pb dating of detrital zircons from the Carboniferous turbidites of southwestern Iberia (the Cabrela, Mértola, Mira, and Brejeira formations) shows that synorogenic sedimentation during the Carboniferous was marked by significant variations in the source areas, involving the denudation of different crustal blocks and a break in synorogenic volcanism. The Visean is characterized by the accumulation of immature turbidites (the Cabrela and Mértola formations and the base of the Mira Formation). These turbidites were probably formed in relation to sources (magmatic arcs) of Mid–Late Devonian age poorly influenced by sedimentary recycling, as indicated by the near-absence of pre-Devonian zircons, ages that are typical of the Gondwana basement. The presence of Carboniferous grains in Visean turbidites indicates that volcanism was active at this time. Later, Serpukhovian to Moscovian turbiditic sedimentation (the Mira and Brejeira formations) included sedimentary detritus derived from mature felsic source rocks situated far from active magmatism. The abundance of Proterozoic and Palaeozoic zircons reveals strong recycling of the pre-Carboniferous basement. A peri-Gondwanan provenance is indicated by zircon populations with Neoproterozoic (the Cadomian–Avalonian and Pan-African zircon-forming events), Palaeoproterozoic, and Archean (the West African Craton zircon-forming events) ages. The presence of Late Ordovician and Silurian detrital zircons in the Brejeira turbidites, which do not correspond to the Gondwana basement of southwestern Iberia, indicates an external source (Laurussia?).